Chalcophile chemistry for enhanced detection of copper in its compounds and minerals. (15th July 2019) - Mehta, Rohan; Zheng, Zhaoyu; Pavlov, Julius; Attygalle, Athula B.
Graphical abstract: Upon laser irradiation, sulfur extracts chemically bound copper from its compounds, and forms Cu x S y − clusters, supporting Goldschmidt's classification that copper is a chalcophile. Moreover, an array of Cu–S ion clusters (with m / z ratios extending to over 8000) are formed when a mixture of copper and sulfur is irradiated with UV light. Abstract: Samples of elemental copper, upon laser irradiation under negative-ion LDI-MS conditions, do not generate noticeable signals for copper-bearing gaseous ions. In contrast, a several thousand-fold enhancement of the generated ion current was observed when freshly made mixtures of copper and sulfur powders were laser-ablated. Time-of-flight mass spectra recorded showed a range of peaks with m / z ratios extending to over m / z 8000, indicating the formation in situ of an array of Cu–S ion clusters by a chemical reaction that takes place between the two elements upon laser irradiation. Evidently, sulfur acts as a potent reactive matrix and generates at least three distinguishable series of ion clusters: Cu1 S x − ( x = 2, 3, 4…), Cu2 S y − ( y = 3, 4, 5…), and Cu3 S z − ( z = 3, 4, 5…). Laser ablation of CuS alone did not produce signals beyond m / z 600. Some of the high-mass ions formed in this manner were isobaric; consequently, composite peaks were observed under low-resolution MS conditions. Under high-resolution conditions, however, we were able to separate and determine the composition of some isobaric mixtures. For example, the peak recorded at m / z 287 was resolved to two peaks that represented primarily the 63 Cu2 65 Cu 32 S3 − and 63 Cu 32 S7 − ions. Intriguingly, the spectra recorded from many copper-containing minerals mixed with sulfur were remarkably similar to those acquired from copper-and-sulfur mixtures, which demonstrated that elemental sulfur has the ability to extract chemically bound copper even from its compounds, and form gas-phase Cu–S clusters of varying composition.